A logarithmically completely monotonic function involving the gamma function and originating from the Catalan numbers and function - Liu, Fang-Fang; Shi, Xiao-Ting; Qi, Feng (Global Journal of Mathematical Analysis, 2015)
In the paper, the authors find necessary conditions and sufficient conditions for a function involving the gamma function and originating from investigation of properties of the Catalan numbers and function in combinatorics to be logarithmically completely monotonic.